NANOMATERIAL BASED ANTIMICROBIAL SYSTEMS FOR INFECTIOUS DISEASE PREVENTION - Raymond Foster; Leon Gittens; Julian Browne (Yayasan Adra Karima Hubbi, 2026)
Nanomaterials have gained significant attention as effective antimicrobial agents for combating infectious diseases due to their unique properties, including high surface area, small size, and enhanced interaction with microbial cells. Traditional antimicrobial therapies, such as antibiotics, have limitations, including the development of resistance, which has spurred the exploration of alternative strategies. This study investigates nanomaterial-based antimicrobial systems, focusing on their efficacy in preventing and treating infections caused by bacteria, fungi, and viruses. The primary aim is to evaluate the antimicrobial properties of various nanomaterials, such as silver nanoparticles, copper oxide nanoparticles, and graphene oxide, and to assess their potential applications in medical devices and surface coatings. The research employs in vitro methods, including disk diffusion assays, minimum inhibitory concentration (MIC) testing, and bacterial growth curve analysis, to evaluate the antimicrobial activity of these nanomaterials. The results show that nanomaterial-based systems exhibit significant antimicrobial activity, with silver nanoparticles demonstrating the highest efficacy in inhibiting bacterial growth, followed by copper oxide and graphene oxide. In conclusion, nanomaterial-based antimicrobial systems offer a promising alternative to traditional antimicrobial treatments, with the potential to address the growing challenge of antimicrobial resistance in infectious diseases.